Brain activity, regional gray matter loss, and decision-making in multiple sclerosis. (August 2018) - Weygandt, Martin; Wakonig, Katharina; Behrens, Janina; Meyer-Arndt, Lil; Söder, Eveline; Brandt, Alexander U; Bellmann-Strobl, Judith; Ruprecht, Klemens; Gold, Stefan M; Haynes, John-Dylan; Paul, Friedemann
Background: Decision-making (DM) abilities deteriorate with multiple sclerosis (MS) disease progression which impairs everyday life and is thus clinically important. Objective: To investigate the underlying neurocognitive processes and their relation to regional gray matter (GM) loss induced by MS. Methods: We used a functional magnetic resonance imaging (fMRI) Iowa Gambling Task to measure DM-related brain activity in 36 MS patients and 21 healthy controls (HC). From this activity, we determined neural parameters of two cognitive stages, a deliberation ("choice") period preceding a choice and a post-choice ("feedback") stage reporting decision outcomes. These measures were related to DM separately in intact and damaged GM areas as determined by a voxel-based morphometry analysis. Results: Severely affected patients (with high lesion burden) showed worse DM-learning than HC ( t = −1.75, p = 0.045), moderately affected (low lesion burden) did not. Activity in the choice stage in intact insular ( t = 4.60, p Family-Wise Error [FWE] corrected = 0.034), anterior cingulate ( t = 4.50, p FWE = 0.044), and dorsolateral prefrontal areas ( t = 4.43, p FWE = 0.049) and in insular areas with GM loss ( t = 3.78, p FWE = 0.011) was positively linked to DM performance across patients with severe tissue damage and HC. Furthermore, activity in intact orbitofrontal areas was positively linked to DM-learning during the feedback stage across these participants ( t = 4.49, p FWE = 0.032). During none of the stages, moderately affected patients showed higher activity than HC, which might have indicated preserved DM due to compensatory activity. Conclusion: We identified dysregulated activity linked to impairment in specific cognitive stages of reward-related DM. The link of brain activity and impaired DM in areas with MS-induced GM loss suggests that this deficit might be tightly coupled to MS neuropathology.